2021
DOI: 10.31234/osf.io/hz593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring psychological constructs in computer-tailored interventions: novel possibilities to reduce participant burden and increase engagement

Abstract: Within the field of health psychology, there has been an enormous increase in behaviour change interventions that use digital technology. Answering questions and providing tailored feedback based on the answers provided by participants is the key working mechanism when using computer-tailoring in behaviour change interventions. This behaviour change method has proven to be (cost-)effective and results in participants being exposed to material that is tailored to their social-cognitive profile. At the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Although demographic variables seem to be the more obvious choice based on our data, the 1-item scale used to assess the stage of decision-making has the major advantage of being easy to use and not requiring participants to complete lengthy questionnaires. By tailoring DAs to the stage of decision-making (as opposed to other constructs or demographic characteristics), it would be possible to alleviate one of the core problems of most contemporary approaches to computer tailoring—that they often impose a significant burden on participants [ 68 ]. The fact that participants’ stage of decision-making had the most consistent effect on the outcomes among the included predictors only adds to this.…”
Section: Discussionmentioning
confidence: 99%
“…Although demographic variables seem to be the more obvious choice based on our data, the 1-item scale used to assess the stage of decision-making has the major advantage of being easy to use and not requiring participants to complete lengthy questionnaires. By tailoring DAs to the stage of decision-making (as opposed to other constructs or demographic characteristics), it would be possible to alleviate one of the core problems of most contemporary approaches to computer tailoring—that they often impose a significant burden on participants [ 68 ]. The fact that participants’ stage of decision-making had the most consistent effect on the outcomes among the included predictors only adds to this.…”
Section: Discussionmentioning
confidence: 99%
“…Motorny et al [298] recently presented a framework that can be used to individualize DAs based on multiple components, such as one's information needs. While promising, their approach could potentially lead to the same problem recently described in the scientific literature in relation to computer-tailored interventions: that computer-tailoring based on multi-item questionnaires can increase participant burden and thereby non-usage attrition as well [284]. Based on the findings from the RCT, a feasible way to offer computer-tailored DAs without increasing participant burden (much) could be to employ the one-item stage of decision making scale as the scale is much shorter than the scales traditionally used within computer-tailored interventions (e.g., [46,71,299,300]).…”
Section: Non-usage Attritionmentioning
confidence: 98%
“…While demographic variables seem like the more obvious choice based on our data, the one-item scale used to assess stage of decision making has the major advantage of being easy to use and not requiring participants to complete lengthy questionnaires. By tailoring DAs to the stage of decision making (as opposed to other constructs or demographic characteristics), it would be possible to alleviate one of the core problems of most contemporary approaches to computer-tailoring, namely that they often impose a significant burden on participants [284]. That participants' stage of decision making had the most consistent effect on the outcomes among the included predictors, only adds to that.…”
Section: Lack Of Statistical Powermentioning
confidence: 99%
“…In terms of computer-tailoring, although this is the usual procedure, studies have shown that participants can be burdened by answering (lengthy) questionnaires for the tailoring process (Alley et al, 2016;Vandelanotte & de Bourdeaudhuij, 2003;Vandelanotte et al, 2004). Therefore, Short et al (2022) discussed new approaches in computer tailoring to increase user engagement and reduce participant burden by reducing or avoiding answering (lengthy) questionnaires, such as by assessing online behavior or sensor data. While data for the tailoring process has generally been collected purposively (e.g., disseminating a questionnaire at baseline), novel ways to use routinely collected data are emerging (Short et al, 2022).…”
Section: Self-report Datamentioning
confidence: 99%
“…Therefore, Short et al (2022) discussed new approaches in computer tailoring to increase user engagement and reduce participant burden by reducing or avoiding answering (lengthy) questionnaires, such as by assessing online behavior or sensor data. While data for the tailoring process has generally been collected purposively (e.g., disseminating a questionnaire at baseline), novel ways to use routinely collected data are emerging (Short et al, 2022). For instance, psychological constructs such as attitude could be inferred based on routinely collected data on online behavior, such as browsing history (Short et al, 2022).…”
Section: Self-report Datamentioning
confidence: 99%